K-38 : (NtBILISI $1 (NeREWAN (B:s (Nsssr(B, (Nrsfsr(B, (NgRUZ(B. (Nsssr(B, (NaZERB(B. (Nsssr(B, (NaRM(B. (Nsssr(B, (NtURCIQ (B/s - (NsUZDALXCEWA(B, (Nn(B.(Na(B.s ((NmOSKWA (B:s (Ngugk(B,s, 1955)
(NoBZORNO(B-(NTOPOGR(B. (NKARTA M(B-(NBA (B1:1000 000, (NL(B. K-38 (NtBILISI $1 (NeREWANs
Keywords: (NnAUKI O zEMLEs; (NkARTOGRAFI^ESKIE PROIZWEDENIQs; (NoBZORNO(B-(NTOPOGRAFI^ESKIE KARTYs; (NsO@Z sOWETSKIH sOCIALISTI^ESKIH rESPUBLIKs; (NrOSSIQs; (NgRUZIQs; (NaZERBAJDVANs; (NaRMENIQs; (NtURCIQs